PENGGUNAAN APLIKASI GOOGLE CLASSROOM UNTUK MOTIVASI DAN HASIL BELAJAR MATERI GEREJA SEBAGAI UMAT ALLAH PADA SISWA KELAS XI IPA SMAN 1 SIBORONGBORONG SEMESTER 1 TAHUN PELAJARAN 2021/2022 - Saidi Perri Marbun (Universitas Negeri Medan, 2023)
This study aims to: 1) To find out an increase in motivation to study Catholic religious education on church material as God's people in class XI IPA students at SMAN 1 Siborongborong Semester 1 Academic Year 2021/2022 through the use of an application based on google classroom. 2) To find out the learning outcomes of Catholic religious education on church material as God's people in class XI IPA students of SMAN 1 Siborongborong Semester 1 of the 2021/2022 Academic Year through the use of a google classroom-based application. This research method uses classroom action research (CAR). The research subjects were students of Class XI IPA at SMAN 1 Siborongborong. The data collection technique uses: 1) observation; 2) Test; 3) Documentation. The results of the study show that: 1) The use of a google classroom-based application for learning Catholic religious education for church materials as God's people can increase student motivation. This is evidenced by an increase in learning motivation from 6 students or 26.09% in the initial study to 15 students or 65.22% in the first cycle and 21 students or 91.30% in the last cycle. 2) The use of google classroom-based applications for learning church materials as God's people can improve student learning outcomes. This is evidenced by the increase in the average initial study learning outcomes of 54.78, in the first cycle the average value obtained by students was 66.52 and in the second cycle the average value obtained by students was 74.78 and was supported by an increase learning completeness in the initial state was 4 students (17.39%), in cycle I it increased to 12 students or 52.17% and in cycle II it increased again to 20 students or 86.96%.